DIFFERENCES IN THE EFFECT OF HEALTH EDUCATION WITH VISUAL AND AUDIOVISUAL MEDIA ON COMMUNITY KNOWLEDGE ABOUT TOGA: Perbedaan Pengaruh Pendidikan Kesehatan Dengan Media Visual dan Audiovisual Terhadap Pengetahuan Masyarakat Tentang TOGA - Rahayu, Eka Putri; Chifdillah, Nino Adib (Preventif : Jurnal Kesehatan Masyarakat, 2025)
Background: Family medicinal plants (TOGA) are one of the people’s choices for planting in their yards, considering that they can be used for health. Apart from that, TOGA is also safe from chemicals, cheap and easy to obtain. Results Riskesdas 2018 stated that the highest percentage of medicinal plant use was ginger 50,36%, galangal 48,77% and meniran 13,93%. In order to improve the level of public health, we can do health education. Health education is always related to the use of health promotion media. The vital function of media is to facilitate the process of conveying and receiving information. Therefore, efforts to improve the level of public health need to utilize various health service efforts, including traditional health. Purpose: This research aims to measure the differences health education media on public knowledge about family medicinal plant. Methods: This research was quantitave with non-equivalent control group design. There were 1 control group and 2 intervention group. This research held in June-August 2021 in Independent Care Group Bumi Rindang Luhur, Samarinda city. The population was 36 respondents who live in Bumi Rindang Luhur Residence. This research used total population as technique sampling. Bivariate statistic used One-Way Annova. Results: Statistical analytic stated that there is difference in the average knowledge score between the three groups with ρ value 0,000 (ρ <α, α=0,05). Conclusion: The importance of outreach activities about family medicinal plant with visual and audiovisual media to the community